Методика прогнозування довговічності фрикційних накладок тракторних гальм - Подригало, Михайло Абович; Кашканов, Андрій Альбертович; Шеїн, Віталій Сергійович; Касьяненко, Олексій Віталійович; Ужик, Валерій Владиславович (Національний технічний університет "Харківський політехнічний інститут", 2021)
В роботі наведені результати дослідження щодо створення методики прогнозування довговічності фрикційних накладок тракторних гальмівних механізмів на стадії проектування. Враховується не тільки збільшення потужності двигуна і маси трактора, але також і встановлення більш удосконалених гальмівних механізмів. Завдяки розробленій методиці прогнозування довговічності фрикційних накладок тракторних гальмівних механізмів, обґрунтовано використання уніфікованих дискових гальм.

The paper presents the results of a research on the creation of a methodology for predicting the durability of friction linings of tractor brake mechanisms at the design stage. Not only an increase in engine power and tractor weight is taken into account, but also the installation of more advanced brake mechanisms. Thanks to the developed method for predicting the durability of the friction linings of tractor brake mechanisms, the use of unified disc brakes is justified. To solve the problem, the similarity theory was used, in which the most intense loading mode of the tractor brake mechanisms was modeled. As an indicator, the maximum work performed by the brakes until the friction linings are completely worn out was used. The results of estimating the resource of the friction linings of the tractor brake mechanisms under the most intense loading conditions were compared with the results of the calculation under the actual loading conditions.
Method for prediction of durability of friction linings of tractor brakes
Keywords: трактор; гальмівні механізми; фрикційні накладки; прогнозування довговічність; самохідне шасі; надійність гальмівних систем; безпека руху тракторів; tractor; brake mechanisms; friction linings; durability prediction; self-propelled chassis; reliability of brake systems; tractor traffic safety